Estimation of Generated Axial Force Considering Rolling–Sliding Friction in Tripod-Type Constant Velocity Joint. Issue 5 (3rd September 2018) - Jo, Gwang Hee; Kim, Seong Han; Kim, Dong Wan; Chu, Chong Nam
ABSTRACT: This study proposes a new generated axial force (GAF) estimation model of tripod-type constant velocity (CV) joints. For development of the model, kinematic analysis was performed to derive the relative coordinates of components and contact points. Through the analysis, the normal load that acts on contact points was also obtained. This study employs two friction models—pure sliding and rolling–sliding—to obtain the friction coefficients on the contact points. Particularly for the rolling–sliding model, this study used the experimental analysis on rolling–sliding ratio and friction coefficients were studied using a tribometer. By introducing two models, this study considers not only the pure sliding friction but also the rolling–sliding friction that occurs between spherical rollers and tracks. This study verifies the GAF estimation model by comparing the simulation results with the experimental results. A tripod-type CV joint was set as a target and its GAF was derived by the model. Then, its actual GAF was measured and the results were compared with each other. A GAF measurement system was set up for the measurement in this study. The estimated results show similar trends with the measured results under low-resistance torque condition and the GAF model provides very accurate estimation under high-resistance torque conditions.